Surface Chemistry of Thiomalic Acid Adsorption on Planar Gold and Gold Nanoparticles - Azcárate, Julio César (2014)
The self-assembly of thiomalic acid (TMA) on Au(111) and on preformed Au nanoparticles (AuNPs) protected by weak ligands has been studied by X-rayphotoelectron spectroscopy (XPS) and electrochemical techniques. Results show that TMA is adsorbed on the Au(111) surface as thiolate species with a small amount of atomic sulfur (∼10%) and a surface coverage lower than that found for alkanethiols due to steric factors. The amount of atomic sulfur markedly increases when the TMA is adsorbed on AuNPs by the ligand exchange method. We propose that the atomic sulfur is produced as a consequence of C−S bondcleavage, a process that is more favorable at defective sites of the AuNPs surface. The bond scission is also assisted by the presence of the electron-withdrawing carboxy moiety in the α-position relative to the C−S bond. Moreover, the high local concentration of positively charged species increases the stability of the negatively charged leaving group, leading to a higher amount of coadsorbed atomic sulfur. Our results demonstrate that the terminal functionalities of thiols are conditioning factors in the final structure and composition of the adlayers.